Simple Physical Interactions Yield Social Self-Organization in Honeybees - Szopek, Martina; Stokanic, Valerin; Radspieler, Gerald; Schmickl, Thomas (Frontiers in Physics, 2021)
Social insect colonies show all characteristics of collective adaptive systems (CAS). Their complex behavioral patterns arise from social interactions that are based on the individuals’ reactions to and interactions with environmental stimuli. We study here how social and environmental factors modulate and bias collective thermotaxis of young honeybees. Therefore, we record their collective decision making in a series of laboratory experiments and derived a mathematical model of the collective decision making in young bees from our empirical observations. This model uses only one free parameter, that combines the ultimate effects of several aspects of the microscopic individual behavioral mechanisms, such as motion behavior, sensory range or contact detection, into one single coefficient. We call this coefficient the “social factor”. Our model is capable of capturing the observed aggregation patterns from our empiric experiments with static environments and of predicting the emergent swarm-intelligent behavior of the system in dynamic environments. Besides the fundamental research aspect in studying CAS, our model enables us to predict the effects of a physical stimulus onto the macroscopic collective decision making that affects several crucial prerequisites for efficient and effective brood production and population growth in honeybee colonies.